Retaining Alkyl Nucleophile Regiofidelity in Transition-Metal-Mediated Cross-Couplings to Aryl Electrophiles - O’Neill, Matthew; Cornella, Josep (Synthesis, 2018)
While the advent of transition-metal catalysis has undoubtedly transformed synthetic chemistry, problems persist with the introduction of secondary and tertiary alkyl nucleophiles into C(sp2) aryl electrophiles. Complications arise from the delicate organometallic intermediates typically invoked by such processes, from which competition between the desired reductive elimination event and the deleterious β-H elimination pathways can lead to undesired isomerization of the incoming nucleophile. Several methods have integrated distinct combinations of metal, ligand, nucleophile, and electrophile to provide solutions to this problem. Despite substantial progress, refinements to current protocols will facilitate the realization of complement reactivity and improved functional group tolerance. These issues have become more pronounced in the context of green chemistry and sustainable catalysis, as well as by the current necessity to develop robust, reliable cross-couplings beyond less explored C(sp2)–C(sp2) constructs. Indeed, the methods discussed herein and the elaborations thereof enable an ‘unlocking’ of accessible topologically enriched chemical space, which is envisioned to influence various domains of application.1 Introduction2 Mechanistic Considerations3 Magnesium Nucleophiles4 Zinc Nucleophiles5 Boron Nucleophiles6 Other Nucleophiles7 Tertiary Nucleophiles8 Reductive Cross-Coupling with in situ Organometallic Formation9 Conclusion
Keywords: β-H elimination; mechanism; cross-coupling; isomerization